Applied Calculus for Business and Economics: With an Introduction to Matrices - Beer, Gerald Alan. (Cambridge, MA: Winthrop Publishers, 1978)
This text serves a dual purpose. First, it can be used simply as a calculus text. Second, since it covers matrices, sigma notation, and significant elements of the mathematics of finance and includes extensive algebra review, it is also suitable for a course in mathematical analysis.
Includes index.
ne 5/03/2018
Loan
Keywords: Calculus; Matrices; Business mathematics; Economics, Mathematical